Correlation between visceral fat, muscles mass, and blood sugar levels in adults - PUTU SARASWATI LAKSMI DEWI; I MADE PANDE DWIPAYANA (HANG TUAH MEDICAL JOURNAL, 2022)
The correlation between visceral fat levels (VF) or muscle mass and insulin resistance or type-2 diabetes mellitus has been studied extensively elsewhere, particularly in the urban-dwelling populations. The current study aimed to evaluate the association of VF or muscle mass with random blood glucose (RBG) among the rural population. A cross-sectional study was conducted in Buleleng Regency. A total of 105 samples were enrolled in the study and obtained through a systematic interview, random blood glucose measurement, anthropometry, and bioelectrical impedance analysis. Spearman’s correlation test was used to determine the correlation between visceral fat levels (VF) or muscle mass with RBG levels. A partial correlation test was used to control confounding variables (age, muscle mass, body mass index, body weight, waist circumference, hip circumference). Most of the samples (61.9%) were female, with a mean age was 53,48 ± 13,03. The statistical analysis results show VF had a significant correlation with RBG (r= 0.363, p<0.001 but neither as role of muscle mass in which the r= -0.073, p=0.461). There was no significant correlation found on the partial correlation test, between VF and RBG. In conclusion, although the correlation between VF levels and RBG was weak, the clinician should aware of the role of VF in the development of insulin resistance or diabetes mellitus type-2.